Chemical Inhibition of Histone Deacetylases 1 and 2 Induces Fetal Hemoglobin through Activation of GATA2 - Shearstone, Jeffrey R.; Golonzhka, Olga; Chonkar, Apurva; Tamang, David; van Duzer, John H.; Jones, Simon S.; Jarpe, Matthew B. (PLOS ONE, 2016)
Therapeutic intervention aimed at reactivation of fetal hemoglobin protein (HbF) is a promising approach for ameliorating sickle cell disease (SCD) and β-thalassemia. Previous studies showed genetic knockdown of histone deacetylase (HDAC) 1 or 2 is sufficient to induce HbF. Here we show that ACY-957, a selective chemical inhibitor of HDAC1 and 2 (HDAC1/2), elicits a dose and time dependent induction of γ-globin mRNA (HBG) and HbF in cultured primary cells derived from healthy individuals and sickle cell patients. Gene expression profiling of erythroid progenitors treated with ACY-957 identified global changes in gene expression that were significantly enriched in genes previously shown to be affected by HDAC1 or 2 knockdown. These genes included GATA2, which was induced greater than 3-fold. Lentiviral overexpression of GATA2 in primary erythroid progenitors increased HBG, and reduced adult β-globin mRNA (HBB). Furthermore, knockdown of GATA2 attenuated HBG induction by ACY-957. Chromatin immunoprecipitation and sequencing (ChIP-Seq) of primary erythroid progenitors demonstrated that HDAC1 and 2 occupancy was highly correlated throughout the GATA2 locus and that HDAC1/2 inhibition led to elevated histone acetylation at well-known GATA2 autoregulatory regions. The GATA2 protein itself also showed increased binding at these regions in response to ACY-957 treatment. These data show that chemical inhibition of HDAC1/2 induces HBG and suggest that this effect is mediated, at least in part, by histone acetylation-induced activation of the GATA2 gene.